Japanese Society for Radiation Oncology Consensus Guidelines of combined intracavitary and interstitial brachytherapy for gynecological cancers. (28th March 2022) - Murakami, Naoya; Ohno, Tatsuya; Toita, Takafumi; Ando, Ken; Ii, Noriko; Okamoto, Hiroyuki; Kojima, Toru; Tsujino, Kayoko; Masui, Koji; Yoshida, Ken; Ikushima, Hitoshi
Abstract: It has been postulated that the combination of intracavitary and interstitial brachytherapy (IC/IS) is effective and safe for large and irregularly shaped uterine cervical cancer patients. However, due to its invasiveness compared to conventional intracavitary brachytherapy (ICBT), it has to be said that the implementation speed of IC/IS is slow. Until now, there have been no guidelines for required equipment, human resources, and procedural guide focusing solely on IC/IS. The purpose of this guideline is to provide radiation oncologists and medical physicists who wish to start IC/IS with practical and comprehensive guidance for a safe IC/IS introduction and to help accelerate the spread of the utilization of IC/IS nationwide. This is the English translation of the Japanese IC/IS Guidelines, and it was created in an effort to share the Japanese approach to the management of locally advanced uterine cervical cancer worldwide.